Argumentos transcendentais e naturalismo: as duas estratégias anticéticas de Strawson - Gelain, Itamar Luís (2008)
This dissertation has for objective to present and analyze the two anti-skeptical strategies of Strawson, called transcendental arguments and naturalism. Therefore, at a first moment, we will begin by distinguishing and characterizing the two types of transcendental arguments - the refutative (elenctic) and the deductive - which appear, respectively, in the two works Individuals and The bounds of sense. At a second moment, only the refutative transcendental argument itself will be analyzed, which is contained in the first work mentioned, and which is used by Strawson to justify the belief of the continuous existence of the objects, the objective of the skeptical question. And, at last, on one hand, will be discussed the critics of Stroud against this anti-skeptical strategy, to know, the transcendental arguments are not enough to face the skepticism, what makes Strawson to abandon the transcendental arguments as anti-skeptical; and on the other hand, naturalism is presented as the new anti-skeptical strategy of Strawson, which would be supported by Hume and Wittgenstein, as well as the new role of the transcendental arguments, taken now as conceptual connectors within the conceptual scheme.